The Recent Decline in Italian Social Services System, Amid Financial Crises and Socio-Political Constraints - Burgalassi, Marco; Melchiorre, Eleonora (European Scientific Journal, ESJ, 2017)
In Italy the social services have always been a marginal part of social protection system and only since the late twentieth century had a development. This development, however, at some time has stopped. The process of â€œliability reductionâ€ of the national government towards the local welfare system and recent cuts in social funding, in fact, have led to a new decline of social services. This essay presents a longitudinal view of the issues that concerned the social services sector over the course of the last two decades. The objective of the analyses is to demonstrate that the recent decline in the social services system is tied to the economic recession of 2008, but was above all caused by the reaffirmation of the traditionally marginal position of social services on the agenda of the national government. The theoretical framework used considers the development of social services of the years of the late twentieth century as a passage of the extension and consolidation process of the Italian system of social protection built since the ’60s. However, in this process the social services was placed at the edge of the main path and this determined the weakness of their position. Thus, the external event represented by the international financial crisis has had a negative impact almost exclusively on social services, while the historical features and the path of structuring of the Italian system of social protection has prevented the same happen for the other sectors (pensions, health).